EKSISTENSI DEWAN PERWAKILAN DAERAH (DPD) DALAM PEMEKARAN DAERAH BERDASARKAN UNDANG-UNDANG DASAR 1945 PASAL 22D - Andyka Rahmat Putra; Gusliana HB; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
As the existence of the Regional Representative Council regional representative bodies have a very important role in fighting for the aspirations of the people in the area, particularly on regional expansion due to the expansion of local government can be useful to accelerate regional development and public service approach, in stages. This has an impact on the improvement of the welfare of the community is the goal of national development. But in fact the DPD has not been able to perform its role to the fullest, especially in the area when the expansion is part of a regional expansion DPD affairs. In fact, the division of the House was most strongly associated with the expansion of the DPD. As an institution representing parts of the provinces throughout Indonesia, DPD also need to regularly monitor the progress of various legislative process at the local level.Keywords: Existence - DPD - Redistricting